2010
DOI: 10.1097/rhu.0b013e3181fe8ba3
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Fasciitis and Myositis Caused by Streptococcal Flesh-Eating Bacteria

Abstract: Three types of group A streptococcal infections are particularly feared: necrotizing fasciitis, myositis, and streptococcal toxic shock syndrome (TSS). We present 3 cases of necrotizing fasciitis due to Streptococcus pyogenes, one in an immunocompromised patient who had received kidney transplant and 2 healthy patients. Mean age of patients was 52 years (range, 42-67 years), and all 3 were male. One spontaneous case in absence of any obvious portal of entry is reported. The clinical course was initially indole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…GAS is also an important cause of post-infectious sequelae such as post-streptococcal glomerulonephritis and rheumatic fever [1], [2], [3], [4]. In contrast, Moraxella catarrhalis is a rather exclusive colonizer and primarily opportunistic pathogen of the human respiratory tract, the bacterium being associated with both upper (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…GAS is also an important cause of post-infectious sequelae such as post-streptococcal glomerulonephritis and rheumatic fever [1], [2], [3], [4]. In contrast, Moraxella catarrhalis is a rather exclusive colonizer and primarily opportunistic pathogen of the human respiratory tract, the bacterium being associated with both upper (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…al. who reported that 2 out of 3 cases of necrotizing fasciitis did not have any risk factors for the condition [14]. Necrotizing fasciitis is classified according to its microbiology i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In SOTRs, streptococcal species are associated with causing a variety of skin infections, such as impetigo contagiosa [5], ecthyma, and NF [33]. Streptococcus pyogenes is the most common pathogen to cause monomicrobial NF [17], though Streptococcus pneumoniae has also caused disease in renal transplant recipients [34].…”
Section: Cutaneous Streptococcal Infectionsmentioning
confidence: 99%